Digitalisierung, Medienbildung und Medienkompetenz. Verhältnisbestimmungen und Implikationen für die Lehrerbildung und den Lehrerberuf. - Herzig, Bardo (Digital?! Perspektiven der Digitalisierung für den Lehrerberuf und die Lehrerbildung (Beiträge zur Lehrerbildung und Bildungsforschung, Band 5))

Medienkompetenz. Modellierung, Messung und Bedeutung in Zeiten der Coronapandemie - Herzig, Bardo (TELEVIZION 33/2020/2)

Two-photon phase-sensing with single-photon detection - Vergyris, Panagiotis; Babin, Charles; Nold, Raphael; Gouzien, Elie; Herrmann, Harald; Silberhorn, Christine; Alibart, Olivier; Tanzilli, Sébastien; Kaiser, Florian (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Bildung in der digitalen Welt. Digitalisierungsbezogene Kompetenzen von Lehrpersonen - Herzig, Bardo (Schulmagazin 5-10: Impulse für kreativen Unterricht)

Medienbildung in der Grundschule - ein konzeptioneller Beitrag zur Auseinandersetzung mit (digitalen) Medien. - Herzig, Bardo (Zeitschrift für Grundschulforschung)

Investigating the Hen-Egg-Problem: A Cross-Lagged-Panel Approach to Informal Workplace Learning and Working Conditions. - Decius, Julian; Schaper, Niclas; Seifert, Andreas (9th PDRnet Research Symposium)

Schulische Medienbildung im Spannungsfeld von Medienpädagogik und Fachdidaktik - Herzig, Bardo; Martin, A. (Medienpädagogik. Zeitschrift für Theorie und Praxis der Medienbildung)

Orientierungen in der digitalen Welt

Sachunterricht begründet planen. Das Prozessmodell Generativer Unterrichtsplanung Sachunterricht (GUS) und seine Grundlagen.

Multiple Points of Operator Semistable Lévy Processes - Luks, Tomasz; Xiao, Yimin (Journal of Theoretical Probability)

Further Extending the Dilution Range of the “Solvent-in-DES” Regime upon the Replacement of Water by an Organic Solvent with Hydrogen Bond Capabilities - Lopez Salas, Nieves; Vicent-Luna, J. M.; Posada, E.; Imberti, S.; Madero-Castro, R. M.; Calero, S.; Ania, C. O.; Jiménez-Riobóo, R. J.; Gutiérrez, M. C.; Ferrer, M. L.; del Monte, F. (ACS Sustainable Chemistry & Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Thin films of poly(vinylidene fluoride-co-hexafluoropropylene)-ionic liquid mixtures as amperometric gas sensing materials for oxygen and ammonia - Lee, Junqiao; Hussain, Ghulam; Lopez Salas, Nieves; MacFarlane, Douglas R.; Silvester, Debbie S. (The Analyst)
A gas sensor comprising of a planar electrode device covered with a thin layer of gel polymer electrolyte gave accurate and fast sensing responses for oxygen and ammonia detection in both the cathodic and anodic potential regions.
Keywords: Electrochemistry; Spectroscopy; Environmental Chemistry; Biochemistry; Analytical Chemistry

Neue Wege der Medizintechnik: RehaToGo - das Ganglabor am Körper - Jäger, M; Rühlemann, A; Kecskemethy, A; Pohl, N; Hoffmann, M; Jöllenbeck, Thomas; Hefter, H; Kaiser, T (Zeitschrift für Orthopädie und Unfallchirurgie)

Project “Schule für alle” as a mentoring programme in university teacher education: Professionalization processes of student teachers in different practical university phases - Kottmann, Brigitte; Pieper, Catania (Hungarian Educational Research Journal)
In the mentoring programme project “Schule für alle” (“School for all”) at the University of Bielefeld in North Rhine-Westphalia, university students of primary or special education support a child who is in a situation of crisis for more than one year. In addition, the university students receive ongoing, systematic university support (cf. Kottmann, 2007, p. 32; Kottmann, 2014, p. 380). The accompanying research by “Schule für alle” focuses on the professionalization processes of student teachers during practical phases at universities; accordingly, control groups were included on a pro rata basis. In the pre-post design, all students completed a questionnaire (cf. Pieper, Kottmann & Miller, 2018, p. 294), the evaluation of which shows few changes in the professional perception of competence. Students of the mentoring programme also regularly reflected on their practical experience. Based on the objective hermeneutics it was discovered that the conception of the project supports the process of perceiving, acknowledging and becoming more sensitive in regard to heterogeneous realities in life (cf. Pieper & Kottmann 2019b, p. 312) and that students can consciously perceive and reflect their own normative expectations (cf. Pieper & Kottmann 2019a, p. 79). The article primarily presents the results of the pre-post survey in detail and adds insights into the qualitative evaluation processes. In the conclusion, the potential of the project and mentoring programmes in general, specifically for teacher training students, is described.
Keywords: professionalization of teacher training students; practical university phases; teacher training at universities; men-toring programmes

Kindliche Lebenswirklichkeit aus der Perspektive von Lehramtsstudierenden: „Ich verstehe jetzt, warum er in der Schule so motiviert ist!“ - Pieper, Catania; Kottmann, Brigitte (Diversität und soziale Ungleichheit. Herausforderungen an die Integrationsleistung der Grundschule)

Die Lernwerkstatt und der Studiengang „Integrierte Sonderpädagogik“ an der Universität Bielefeld: Impulse, Synergien und Reflexionen - Kottmann, Brigitte; Alena, Lensker (Hochschullernwerkstätten – Elemente von Hochschulentwicklung? Ein Rückblick auf 15 Jahre Hochschullernwerkstatt in Halle und andernorts)

Lehrideale und ihre Rolle in der (Ver-)Achtung der Pädagogik - Vochatzer, Stefanie (Friedrich Wilhelm Dörpfeld Lehrerideale im 19. Jahrhundert)

Roadmap on quantum light spectroscopy - Mukamel, Shaul; Freyberger, Matthias; Schleich, Wolfgang; Bellini, Marco; Zavatta, Alessandro; Leuchs, Gerd; Silberhorn, Christine; Boyd, Robert W; Sánchez-Soto, Luis Lorenzo; Stefanov, André; Barbieri, Marco; Paterova, Anna; et al. (Journal of Physics B: Atomic, Molecular and Optical Physics)
Keywords: Condensed Matter Physics; Atomic and Molecular Physics; and Optics

Single-photon sources: Approaching the ideal through multiplexing - Meyer-Scott, Evan; Silberhorn, Christine; Migdall, Alan (Review of Scientific Instruments)
Keywords: Instrumentation

Improper Gaussian Signaling for the $K$-User MIMO Interference Channels With Hardware Impairments - Soleymani, Mohammad; Santamaria, Ignacio; Schreier, Peter J (IEEE Transactions on Vehicular Technology)

Two-channel passive detection of cyclostationary signals - Horstmann, Stefanie; Ramírez, David; Schreier, Peter J (IEEE Transactions on Signal Processing)

Distillation of squeezing using an engineered pulsed parametric down-conversion source - Dirmeier, Thomas; Tiedau, Johannes; Khan, Imran; Ansari, Vahid; Müller, Christian R.; Silberhorn, Christine; Marquardt, Christoph; Leuchs, Gerd (Optics Express)
Hybrid quantum information processing combines the advantages of discrete and continues variable protocols by realizing protocols consisting of photon counting and homodyne measurements. However, the mode structure of pulsed sources and the properties of the detection schemes often require the use of optical filters in order to combine both detection methods in a common experiment. This limits the efficiency and the overall achievable squeezing of the experiment. In our work, we use photon subtraction to implement the distillation of pulsed squeezed states originating from a genuinely spatially and temporally single-mode parametric down-conversion source in non-linear waveguides. Due to the distillation, we witness an improvement of 0.17 dB from an initial squeezing value of −1.648 ± 0.002 dB, while achieving a purity of 0.58, and confirm the non-Gaussianity of the distilled state via the higher-order cumulants. With this, we demonstrate the source’s suitability for scalable hybrid quantum network applications with pulsed quantum light.
Keywords: Atomic and Molecular Physics; and Optics

Die Wiedereinrichtung der Dombauhütten in Europa im 19. und 20. Jahrhundert - Silvestri, Marco; Seng, Eva- Maria (Le chantier cathédral en Europe. Diffusion et sauvegarde des savoirs, savoir-faire et matériaux du Moyen Âge à nos jours)

Mathematical Analysis of Two Competing Cancer Cell Migration Mechanisms Driven by Interstitial Fluid Flow - Steiner, Evi; Winkler, Michael (Journal of Nonlinear Science)

Einladung an Unbekannt und nicht-identitäre Frömmigkeit. Die Bedeutung von Kirchentagen für die Praxis evangelischer Spiritualität - Schroeter-Wittke, Harald (Handbuch Evangelische Spiritualität. Band 3: Praxis)

70 Jahre Kirchentag. Eine musikalische Zeitreise vom Bläserruf bis zum Abendsegen - Schroeter-Wittke, Harald; Fuhrmann, Christian; Greim, Ulrike; Groscurth, Reinhard (Deutscher Evangelischer Kirchentag Dortmund 2019. Dokumente)

Wie klingt, was du glaubst? Ouvertüre und Nachklang zur Leipziger Disputation 1519 - Schroeter-Wittke, Harald (Praktische Theologie)

Licht vom Licht – Tigran Hamasyans Luys i Luso. Zum 150. Geburtstag von Komitas - Schroeter-Wittke, Harald (Praktische Theologie)

Finding Gabriel. Zum 50. Geburtstag von Brad Mehldau - Schroeter-Wittke, Harald (Praktische Theologie)

Bibel als Klangraum - Bibliodrama und Musik - Schroeter-Wittke, Harald (Text-Raum)

David J. Burn, Grantley R. McDonald, Joseph Verheyden, Peter De Mey (ed.), Music and Theology in the European Reformations, Turnhout (Brepols) 2019 - Schroeter-Wittke, Harald (Francia recensio)

High cycle life all-solid-state fluoride ion battery with La 2 NiO 4+d high voltage cathode - Nowroozi, Mohammad Ali; Wissel, Kerstin; Donzelli, Manuel; Hosseinpourkahvaz, Niloofar; Plana-Ruiz, Sergi; Kolb, Ute; Schoch, Roland; Bauer, Matthias; Malik, Ali Muhammad; Rohrer, Jochen; Ivlev, Sergei; Kraus, Florian; et al. (Communications Materials)
Abstract Fluoride ion batteries (FIBs) are a recent alternative all-solid-state battery technology. However, the FIB systems proposed so far suffer from poor cycling performance. In this work, we report La 2 NiO 4.13 with a Ruddlesden-Popper type structure as an intercalation-based active cathode material in all solid-state FIB with excellent cycling performance. The critical charging conditions to maintain the conductivity of the cell were determined, which seems to be a major obstacle towards improving the cycling stability of FIBs. For optimized operating conditions, a cycle life of about 60 cycles and over 220 cycles for critical cut-off capacities of 50 mAh/g and 30 mAh/g, respectively, could be achieved, with average Coulombic efficiencies between 95 – 99%. Cycling of the cell is a result of fluorination/de-fluorination into and from the La 2 NiO 4+d cathode, and it is revealed that La 2 NiO 4.13 is a multivalent electrode material. Our findings suggest that La 2 NiO 4.13 is a promising high energy cathode for FIBs.
Keywords: Mechanics of Materials; General Materials Science

8. Sonntag nach Trinitatis (2.8.1010). Joh 9,1-7: Schaffe Licht in dunkler Nacht - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Zur Relationalität des Gestischen – über den Zusammenhang von Körpern, Kleidern und Bewegung - Haller, Melanie; de Smit, Peer; Darian (Hg.), Veronika (Out of Line. Perspektiven gestischer Forschung, Berlin: Neofelis.)

Intersystem Crossing and Triplet Dynamics in an Iron(II) N-Heterocyclic Carbene Photosensitizer - Zobel, J. Patrick; Bokareva, Olga S.; Zimmer, Peter; Wölper, Christoph; Bauer, Matthias; González, Leticia (Inorganic Chemistry)
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Revealing Hot and Long-Lived Metastable Spin States in the Photoinduced Switching of Solvated Metallogrid Complexes with Femtosecond Optical and X-ray Spectroscopies - Naumova, Maria A.; Kalinko, Aleksandr; Wong, Joanne W. L.; Abdellah, Mohamed; Geng, Huifang; Domenichini, Edoardo; Meng, Jie; Gutierrez, Sol Alvarez; Mante, Pierre-Adrien; Lin, Weihua; Zalden, Peter; Galler, Andreas; et al. (The Journal of Physical Chemistry Letters)
Keywords: General Materials Science; Physical and Theoretical Chemistry

Exploring the light-induced dynamics in solvated metallogrid complexes with femtosecond pulses across the electromagnetic spectrum - Naumova, Maria A.; Kalinko, Aleksandr; Wong, Joanne W. L.; Alvarez Gutierrez, Sol; Meng, Jie; Liang, Mingli; Abdellah, Mohamed; Geng, Huifang; Lin, Weihua; Kubicek, Katharina; Biednov, Mykola; Lima, Frederico; et al. (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Improving scenario-technique by a semi-automatized consistency assessment based on pattern recognition by artificial neural networks - Gräßler, Iris; Scholle, Philipp; Thiele, Henrik (Proceedings of the DESIGN 2020 16th International Design Conference; 26. - 29. Okt. 2020)

Solidarität vs. Ressourcensouveränität? Die dritte Seerechtskonferenz als Herausforderung für die Süd-Süd-Beziehungen - Sackel, Johanna (Nord/Süd Perspektiven auf eine globale Konstellation)

Customer inertia marketing - Henderson, Conor M.; Steinhoff, Lena; Harmeling, Colleen M.; Palmatier, Robert W. (Journal of the Academy of Marketing Science)
Keywords: Marketing; Economics and Econometrics; Business and International Management

Toward a comprehensive framework of value proposition development: From strategy to implementation - Payne, Adrian; Frow, Pennie; Steinhoff, Lena; Eggert, Andreas (Industrial Marketing Management)
Keywords: Marketing

Data Privacy in Retail - Martin, Kelly D.; Kim, Jisu J.; Palmatier, Robert W.; Steinhoff, Lena; Stewart, David W.; Walker, Beth A.; Wang, Yonggui; Weaven, Scott K. (Journal of Retailing)
Keywords: Marketing

Understanding and managing customer value propositions: Introduction to the special issue - Eggert, Andreas; Frow, Pennie; Payne, Adrian; Steinhoff, Lena (Industrial Marketing Management)
Keywords: Marketing

Commentary: Opportunities and challenges of technology in relationship marketing - Steinhoff, Lena; Palmatier, Robert W. (Australasian Marketing Journal)
Keywords: Marketing; Economics and Econometrics

 Zeitschrift für Romanische Sprachen und ihre Didaktik

Photonic Analog-to-Digital-Converters – Comparison of a MZM-Sampler with an Optoelectronic Switched-Emitter-Follower Sampler - Weizel, Maxim; Kaertner, Franz X.; Witzens, Jeremy; Scheytt, J. Christoph (Photonic Networks; 21th ITG-Symposium)

Experimental and Theoretical Study on the Role of Monomeric vs Dimeric Rhodium Oxazolidinone Norbornadiene Complexes in Catalytic Asymmetric 1,2- and 1,4-Additions - Kirchhof, Manuel; Gugeler, Katrin; Fischer, Felix Richard; Nowakowski, Michal; Bauer, Alina; Alvarez-Barcia, Sonia; Abitaev, Karina; Schnierle, Marc; Qawasmi, Yaseen; Frey, Wolfgang; Baro, Angelika; Estes, Deven P.; et al. (Organometallics)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry

Charge Distribution in Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes: A Combined X-ray, XAS, XES, DFT, Mössbauer, and Catalysis Approach - Benedikter, Mathis; Musso, Janis; Kesharwani, Manoj K.; Sterz, K. Leonard; Elser, Iris; Ziegler, Felix; Fischer, Felix; Plietker, Bernd; Frey, Wolfgang; Kästner, Johannes; Winkler, Mario; van Slageren, Joris; et al. (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Electronic Structure of the Hieber Anion [Fe(CO)3(NO)]− Revisited by X-ray Emission and Absorption Spectroscopy - Burkhardt, Lukas; Vukadinovic, Yannik; Nowakowski, Michał; Kalinko, Aleksandr; Rudolph, Julian; Carlsson, Per-Anders; Jacob, Christoph R.; Bauer, Matthias (Inorganic Chemistry)
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Stereoselective Chromium‐Catalyzed Semi‐Hydrogenation of Alkynes - Gregori, Bernhard J.; Nowakowski, Michal; Schoch, Anke; Pöllath, Simon; Zweck, Josef; Bauer, Matthias; Jacobi von Wangelin, Axel (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

The role of caregivers in keeping a child-robot interaction going. - Rohlfing, Katharina; Grimminger, Angela; Wrede, Britta (International perspectives on digital media and early literacy: The impact of digital devices on learning, language acquisition and social interaction.)

Ethical Considerations of Applying Robots in Kindergarten Settings: Towards an Approach from a Macroperspective - Tolksdorf, Nils F.; Siebert, Scarlet; Zorn, Isabel; Horwath, Ilona; Rohlfing, Katharina J. (International Journal of Social Robotics)
In child–robot interaction (cHRI) research, many studies pursue the goal to develop interactive systems that can be applied in everyday settings. For early education, increasingly, the setting of a kindergarten is targeted. However, when cHRI and research are brought into a kindergarten, a range of ethical and related procedural aspects have to be considered and dealt with.While ethical models elaborated within other human–robot interaction settings, e.g., assisted living contexts, can provide some important indicators for relevant issues, we argue that it is important to start developing a systematic approach to identify and tackle those ethical issues which rise with cHRI in kindergarten settings on a more global level and address the impact of the technology from a macroperspective beyond the effects on the individual. Based on our experience in conducting studies with children in general and pedagogical considerations on the role of the institution of kindergarten in specific, in this paper,we enfold some relevant aspects that have barely been addressed in an explicit way in current cHRI research. Four areas are analyzed and key ethical issues are identified in each area: (1) the institutional setting of a kindergarten, (2) children as a vulnerable group, (3) the caregivers’ role, and (4) pedagogical concepts. With our considerations, we aim at (i) broadening the methodology of the current studies within the area of cHRI, (ii) revalidate it based on our comprehensive empirical experience with research in kindergarten settings, both laboratory and real-world contexts, and (iii) provide a framework for the development of a more systematic approach to address the ethical issues in cHRI research within kindergarten settings.
Keywords: Robot ethics · Kindergarten settings · Child–robot interaction · Early childhood education

Wie meinst du das? - Begriffserwerb im Religionsunterricht - Kohlmeyer, Theresa; Reis, Oliver; Viertel, Franziska; Rohlfing, Katharina (Theo Web)

International Perspectives on Digital Media and Early Literacy

Ethical considerations of applying robots in kindergarten settings: Towards an approach from a macroperspective. - Tolksdorf, Nils Frederik; Siebert, Scarlet; Zorn, Isabel; Horwarth, Ilona; Rohlfing, Katharina (International Journal of Social Robotics)

Spatially single mode photon pair source at 800 nm in periodically poled Rubidium exchanged KTP waveguides - Eigner, Christof; Padberg, Laura; Santandrea, Matteo; Herrmann, Harald; Brecht, Benjamin; Silberhorn, Christine (Optics Express)

Integrated Communication System: Gesture and language acquisition in typically developing children and children with LD and DLD - Lüke, Carina; Ritterfeld, Ute; Grimminger, Angela; Rohlfing, Katharina; Liszkowski, Ulf (Frontiers in Psychology 11)

Sexuelle Vielfalt in der Religionspädagogik - Uppenkamp, Vera (Inklusive Religionspädagogik der Vielfalt. Konzeptionelle Grundlagen und didaktische Konkretionen)

Armut und Reichtum - Uppenkamp, Vera (Inklusive Religionspädagogik der Vielfalt. Konzeptionelle Grundlagen und didaktische Konkretionen)

Hören – Sprechen – Lesen – Schreiben. Basale Sprachfähigkeiten. - Topalović, Elvira; Uhl, Benjamin

Hören – Sprechen – Lesen – Schreiben. Basale Sprachfähigkeiten. - Topalović, Elvira; Uhl, Benjamin

Digitales Lesen

"Nous sommes embarqués" oder "Wie wir wurden, was wir sind, indem wir hörten, was die Tonträger uns zutrugen" - Kurze Anmerkungen zu Musik, Kultur und Wissenschaft. - Jacke, Christoph (Texturen. Nr. 7 - Wandeln.)

SJS80CJ - Perspektiven und Perspektiven auf Perspektiven auf/in/aus Kulturen. - Jacke, Christoph (Festschrift für Siegfried J. Schmidt zum 80. Geburtstag. Private Festschrift.)

„I Am Just A Broken Heart” – Zum Tod von Dave Kusworth - Jacke, Christoph (Kaput - Magazin für Insolvenz & Pop.)

Differenz - Kammeyer, Katharina (Inklusive Religionspädagogik der Vielfalt. Konzeptionelle Grundlagen und didaktische Konkretionen)

Multimodal approach towards understanding the changes in the autonomic nervous system induced by an ultramarathon. - Vieluf, S; Scheer, V; Hasija, Tanuj; Schreier, PJ; Reinsberger, Claus (Res Sports Med)

Golf spielen gegen die Vergesslichkeit: Effekte des Erlernens der Sportart auf das Default Mode Netzwerk des Gehirns - Ströhlein, Julia Kristin; Vieluf, Solveig; van den Bongard, Franziska; Gölz, Christian Johannes; Reinsberger, Claus (B&G Bewegungstherapie und Gesundheitssport)
Zusammenfassung Einleitung Im Rahmen der Demenz vom Alzheimer-Typ (DAT) zeigt sich eine gestörte neuronale Netzwerkorganisation, welche sich unter anderem auch im Default Mode Netzwerk (DMN) widerspiegelt. Multimodale Interventionen, wie zum Beispiel Golf, können einen positiven Einfluss auf die funktionelle Integrität der Netzwerke haben. Methodik Im Rahmen einer Pilotstudie wurde der Einfluss des Erlernens der Sportart Golf bei sieben älteren Menschen (> 60 Jahre) mit subjektiven Gedächtnisbeschwerden auf die funktionelle Konnektivität des DMN untersucht. Die Probanden haben 22 Wochen unter Anleitung eines professionellen Golftrainers dreimal wöchentlich je 60 min trainiert. Vor (Messzeitpunkt 0, MZP0) und nach der Intervention (Messzeitpunkt 1, MZP1) wurde eine Elektroenzephalografie (EEG)-Messung unter Ruhebedingungen (resting-state) durchgeführt. Die EEG-Daten wurden mit einem Magnetresonanztomographie-Template koregistriert. Die Konnektivitätsanalyse wurde in 15 Regionen des DMN durchgeführt und im Längsschnitt verglichen. Dabei wurden die Frequenzbänder beta (14–29 Hz) und theta (5–7 Hz) berücksichtigt. Ergebnisse Nach der Intervention wurde eine höhere funktionelle Konnektivität im gesamten DMN bei 5 / 7 Teilnehmenden im beta Frequenzband bzw. bei 6 / 7 Probanden im theta Frequenzband zu MZP1 im Vergleich zu MZP0 gemessen. Im anterioren DMN war bei allen Probanden und Probandinnen die funktionelle Konnektivität im beta Frequenzband zu MZP1 im Vergleich zu MZP 0 höher, während sie im theta-Band bei 6 von 7 Teilnehmenden niedriger war. Im posterioren DMN war bei 6 von 7 (beta), bzw. 5 von 7 (theta) Probanden und Probandinnen die funktionelle Konnektivität zu MZP1 höher als zu MZP0. Spearman-Korrelationsanalysen zeigen zudem einen Zusammenhang zwischen der Teilnahmehäufigkeit und der prozentualen Veränderung der funktionellen Konnektivität im gesamten DMN des beta Frequenzbandes (r = 0,786, p = 0,036) und im anterioren DMN des theta Frequenzbandes (r = –0,821, p = 0,023). Fazit Auf Basis der vorliegenden Daten lässt sich vermuten, dass das Erlernen der Sportart Golf einen Einfluss auf das DMN haben könnte. Die Ergebnisse bilden die Grundlage für die Planung einer Studie mit einer größeren Kohorte und randomisierten kontrollierten Design.

Effects of force level and task difficulty on force control performance in elderly people - Strote, Caren; Gölz, Christian Johannes; Stroehlein, Julia Kristin; Haase, Franziska Katharina; Koester, Dirk; Reinsberger, Claus; Vieluf, Solveig (Experimental Brain Research)
Abstract As the proportion of people over 60 years of age rises continuously in westernized societies, it becomes increasingly important to better understand aging processes and how to maintain independence in old age. Fine motor tasks are essential in daily living and, therefore, necessary to maintain. This paper extends the existing literature on fine motor control by manipulating the difficulty of a force maintenance task to characterize performance optima for elderly. Thirty-seven elderly ( M = 68.00, SD = 4.65) performed a force control task at dynamically varying force levels, i.e. randomly changing every 3 s between 10%, 20%, and 30% of the individual’s maximum voluntary contraction (MVC). This task was performed alone or with one or two additional tasks to increase task difficulty. The force control characteristics accuracy, variability, and complexity were analyzed. Lowest variability was observed at 20%. Accuracy and complexity increased with increasing force level. Overall, increased task difficulty had a negative impact on task performance. Results support the assumption, that attention control has a major impact on force control performance in elderly people. We assume different parameters to have their optimum at different force levels, which remain comparably stable when additional tasks are performed. The study contributes to a better understanding of how force control is affected in real-life situations when it is performed simultaneously to other cognitive and sensory active and passive tasks.
Keywords: General Neuroscience

Self-lubricating coatings via PDMS micro-gel dispersions - Ressel, Joerg; Seewald, Oliver; Bremser, Wolfgang; Reicher, Hans-Peter; Strube, Oliver I. (Progress in Organic Coatings)

Contrast variation of micelles composed of Ca2+ and block copolymers of two negatively charged polyelectrolytes - Carl, Nico; Prévost, Sylvain; Schweins, Ralf; Huber, Klaus (Colloid and Polymer Science)
Abstract Block copolymers were prepared with two anionic polyelectrolyte blocks: sodium polyacrylate (PA) and sodium polystyrene sulfonate (PSS), in order to investigate their phase behavior in aqueous solution in the presence of Ca 2+ cations. Depending on the concentration of polymer and Ca 2+ and on the ratio of the block lengths in the copolymer, spherical micelles were observed. Micelle formation arises from the specific interaction of Ca 2+ with the PA block only. An extensive small-angle scattering study was performed in order to unravel the structure and dimensions of the block copolymer micelles. Deuteration of the PA block enabled us to perform contrast variation experiments using small-angle neutron scattering at variable ratios of light and heavy water which were combined with information from small-angle X-ray scattering and dynamic light scattering.
Keywords: Materials Chemistry; Colloid and Surface Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry

The Molecular Mechanism of Polymer Formation of Farnesylated Human Guanylate-binding Protein 1 - Sistemich, Linda; Kutsch, Miriam; Hämisch, Benjamin; Zhang, Ping; Shydlovskyi, Sergii; Britzen-Laurent, Nathalie; Stürzl, Michael; Huber, Klaus; Herrmann, Christian (Journal of Molecular Biology)
Keywords: Molecular Biology; Structural Biology

Self‐Assembly of Pseudo‐Isocyanine Chloride as a Sensor for Macromolecular Crowding In Vitro and In Vivo - Hämisch, Benjamin; Pollak, Roland; Ebbinghaus, Simon; Huber, Klaus (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Self‐Assembly of Pseudo‐Isocyanine Chloride as a Sensor for Macromolecular Crowding In Vitro and In Vivo - Hämisch, Benjamin; Pollak, Roland; Ebbinghaus, Simon; Huber, Klaus (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Sport and Physical Activity in Epilepsy. - van den Bogard, F; Hamer, HM; Sassen, R; Reinsberger, Claus (Dtsch Arztebl Int)

Autonomic nervous system changes detected with peripheral sensors in the setting of epileptic seizures. - Vieluf, S; Reinsberger, Claus; El Atrache, R; Jackson, M; Schubach, S; Ufongene, C; Loddenkemper, T; Meisel, C (Sci Rep)

Match Situations Leading to Head Injuries in Professional Male Football (Soccer)-A Video-Based Analysis Over 12 Years. - Beaudouin, F; Aus der Fünten, K; Tröß, T; Reinsberger, Claus; Meyer, T (Clin J Sport Med)

Neurology - Reinsberger, Claus (Injury and health risk management in sports - a guide to decision making)

Kat.-Nr.23. Nigerianische Helmmaske - Duschner, Paul (Geschichte der Dinge. Zur Herkunft der Objekte in nordrhein-westfälischen Sammlungen)

3. Alles unter dem Himmel - Das Museum für Ostasiatische Kunst in Köln. Köln 2019. Hrsg. Museum für Ostasiatische Kunst Köln. Texte von Adele Schlombs, Christel und Dieter Schürzeberg, Helwig Schmidt-Glintzer, u.a. - Duschner, Paul (Ostasiatische Zeitschrift)

27. Regionalgeschichtstagung: Mythos und historische Wahrheit – ein prekäres Verhältnis - Duschner, Paul (Paderborner Historische Mitteilungen)

Ostasiatika in Paderborn: Zur Sammlung Sigrid Tenge-Erb und Richard Erb - Duschner, Paul (Paderborner Historische Mitteilungen)

Development of a special specimen geometry for the experimental determination of fracture mechanical parameters of clinchable metal sheets - Weiß, Deborah; Schramm, Britta; Kullmer, Gunter

Experimental and numerical preliminary investigations of the base material and preformed components regarding fatigue crack growth in joined structures - Weiß, Deborah; Schramm, Britta; Kullmer, Gunter

Postoperative Versorgung des Charcot-Fußes mittels Unterschenkelorthese – aktueller Stand der Versorgung und Perspektiven der additiven Fertigung - Schafran, Tommy; Schraeder, Dirk Theodor; Schramm, Britta; Kullmer, Gunter

Westfalen in der Vormoderne. Studien zur mittelalterlichen und frühneuzeitlichen Landesgeschichte, 32 Bde.

Wirkungsmessung bei sozialen Sportprojekten im Kontext der Entwicklungszusammenarbeit: Methodische Überlegungen und Herausforderungen. - Petry, K.; Bauer, K.; Biermann, Marie (Sport im Kontext von internationaler Zusammenarbeit und Entwicklung: Perspektiven und Herausforderungen im Spannungsfeld von Wissenschaft, Politik und Praxis.)

11kW, 70kHz LLC Converter Design with Adaptive Input Voltage for 98% Efficiency in an MMC - Unruh, Roland; Schafmeister, Frank; Böcker, Joachim (2020 IEEE 21st Workshop on Control and Modeling for Power Electronics (COMPEL))
Although there are numerous design methodologies for the LLC resonant converter, they often do not consider the possibility of input voltage adjustment. In the proposed concept, a modular multi-level converter (MMC) is used to step-down the three-phase medium voltage of 10 kV, and provide up to 1 MW of pure DC power to the load consisting of electrolyzers for hydrogen generation. Therefore, each module is extended by an LLC resonant converter to adapt to the specific electrolyzers DC voltage range of 142...220 V and to provide galvanic isolation. In order to achieve a high efficiency for a wide range of load conditions, the input voltage of the LLC converter is adjusted between 600 V and 770 V while operating at resonance or close to resonance. The parameters of the 11kW LLC resonant converter with an integrated leakage inductance are systematically optimized to maximize the efficiency for all loads while achieving zero-voltage switching. For a fast estimation of eddy current losses, a new method is proposed, which uses a single FEM simulation to fit newly developed loss equations. The calculated average efficiency is 97.8%. The prototype of the LLC converter reaches a peak efficiency of over 98% at resonance at half load which is similar to the precalculated value.

Integrierte Modellierung von Zuverlässigkeit und dynamischem Verhalten mechatronischer Systeme - Kaul, Thorben
Die digitale Transformation prägt die Entwicklung intelligenter technischer Systeme, welche durch Vernetzung und inhärente Intelligenz einen weiten Funktionsumfang aufweisen. Selbstoptimierende Systeme sind als Stellvertreter der Klasse intelligenter Systeme durch die autonome zielkonforme Adaption des Systemverhaltens charakterisiert. Dabei stellen mechatronische Systeme eine der Grundlagen dieser Systemklasse dar, indem die Umwelt- und Betriebsbedingungen sowie die Systemzustände sensorisch erfasst und das dynamische Systemverhalten zielgerichtet beeinflusst werden. Der große Funktionsumfang intelligenter technischer Systeme geht mit einer Zunahme der Systemkomplexität einher, die eine Herausforderung bei der Absicherung der Verlässlichkeit darstellt. Dem gegenüber bieten insbesondere selbstoptimierende Systeme Potenziale zur Steigerung der Verlässlichkeit. Die Umsetzung entsprechender Maßnahmen erfordert die Unterstützung des Entwicklungsprozesses durch geeignete Methoden. Die Beherrschung der zunehmenden Systemkomplexität ist durch die Verwendung vorhandener Modelle des Entwicklungsprozesses möglich, wird aber in aktuellen Methoden nicht umfänglich genutzt. Das Ziel ist die Absicherung der Verlässlichkeit bereits in frühen Entwicklungsphasen bis hin in späte Lebenszyklusphasen. Es wird eine Methode für die integrierte Modellierung der Zuverlässigkeit, als zentrale Kenngröße der Verlässlichkeit, und des dynamischen Systemverhaltens entwickelt. Anhand von drei Anwendungsbeispielen wird gezeigt, dass diese Methode die Entwicklung von Maßnahmen zur Steigerung der Verlässlichkeit in selbstoptimierenden Systemen ermöglicht, auf komplexe Systeme anwendbar ist und die Absicherung der Verlässlichkeit während des Betriebs mit Hilfe eines Digitalen Zwillings unterstützt.
Keywords: Integrierte Modellierung; geschlossene Modellierung; mechatronische Systeme; intelligente Systeme; Zuverlässigkeit; Dynamische Bayes’sche Netze; Verlässlichkeit; Systemzuverlässigkeit; Digitaler Zwilling; selbstoptimierende Systeme; Mehrzieloptimierung

Kurzzeitaustenitisierung höchstfester Stähle – eine zeiteffiziente Methode zur Fertigung sicherheitsrelevanter Bauteile mit verbesserten Eigenschaften - Andreiev, Anatolii

Development of SLM Ni-based Superalloys and Investigation of Corrosion Behavior in Chloride-containing Environments - Wooldridge, Madison

Properties of bright squeezed vacuum at increasing brightness - Sharapova, Polina R.; Frascella, G.; Riabinin, M.; Pérez, A. M.; Tikhonova, O. V.; Lemieux, S.; Boyd, R. W.; Leuchs, G.; Chekhova, M. V. (Physical Review Research)
Keywords: General Engineering

Spatial entanglement and state engineering via four-photon Hong–Ou–Mandel interference - Ferreri, A; Ansari, V; Brecht, Benjamin; Silberhorn, Christine; Sharapova, Polina R. (Quantum Science and Technology)
Abstract The phenomenon of entanglement is the basis of quantum information and quantum communication processes. Entangled systems with a large number of photons are of great interest at present because they provide a platform for streaming technologies based on photonics. In this paper we present a device which operates with four-photons and based on the Hong–Ou–Mandel interference. The presented device allows to maximize the degree of spatial entanglement and generate the highly entangled four-dimensional Bell states. Furthermore, the use of the interferometer in different regimes leads to fast interference fringes in the coincidence probability with period of oscillations twice smaller than the pump wavelength. We have a good agreement between theoretical simulations and experimental results.
Keywords: Electrical and Electronic Engineering; Physics and Astronomy (miscellaneous); Materials Science (miscellaneous); Atomic and Molecular Physics; and Optics

Inklusion im Kinder- und Jugendsport unter besonderer Berücksichtigung der Heterogenitätsdimension Behinderung. - Radtke, Sabine; Adolph-Börs, Cindy (Vierter Deutscher Kinder- und Jugendsportbericht. Gesundheit, Leistung und Gesellschaft.)

Lernaufgaben im inklusiven Sprachunterricht. - Topalović, Elvira; Uhl, Benjamin (Inklusion und Kooperation. Fördermagazin Grundschule)

Digitales Lesen: Empirische Evidenzen für den Deutschunterricht - Topalović, Elvira (Der Deutschunterricht)

Sprachliches und literarisches Lernen mit Texten in einfacher Sprache. Deutschdidaktische Kontroversen am Beispiel des Romans „Tschick“. - Topalović, Elvira; Diederichs, Lara (Sprache als Herausforderung – Literatur als Ziel. Kinder- und jugendliterarische Texte und Medien als Ressource für sprachsensibles Lernen.)

Wortgruppen entdecken. - Lang, Susanne; Topalović, Elvira (Praxis Deutsch)

Die Wortgruppe als Rechtschreib- und Lesestrategie. - Topalović, Elvira; Lang, Susanne (In: Lernen lernen. Fördermagazin Grundschule)

Crux of Using the Cascaded Emission of a Three-Level Quantum Ladder System to Generate Indistinguishable Photons - Schöll, E; Schweickert, L; Hanschke, L; Zeuner, K.D; Sbresny, F; Lettner, T; Trivedi, R; Reindl, M; Covre da Silva, S.F; Trotta, R; Finley, J.J; Vučković, J; et al.